(untitled) (Journal of Naval Architecture and Marine Engineering, 2017)
It is sound recognized that when the tube is forced to vibrate or is naturally excited to sufficient amplitudes by flow-induced forces, cyclones peeling phenomena arises at downstream of a tube which clues to vibration in the tube. Two-dimensional numerical recreation model for the computation of flow induced vibration of heat exchanger tube bundle imperiled to cross- flow is proficient in current research. Computational Fluid Dynamics (CFD) tool, GAMBIT (grid generation) and ANSYS FLUENT (fluid flow analysis) are operated during numerical investigations. k-epsilon model is used to solve the Navier Stokes equations. Lift coefficient graph derived from analysis is used to predict the vortex shedding frequency using Fast Fourier Transform (FFT). The results of flow rate, Strouhal number, Reduced velocity, Natural frequency of tube as found from the experimental data has been verified numerically for a Reynolds number range of 4.45 × 104<Re <4.65 × 104 . It is concluded that experimental results are well in agreement with the numerical results.